Sofosbuvir and daclatasvir therapy in patients with hepatitis C‐related advanced decompensated liver disease (MELD ≥ 15). Issue 3 (5th December 2017) - McCaughan, G. W.; Thwaites, P. A.; Roberts, S. K.; Strasser, S. I.; Mitchell, J.; Morales, B.; Mason, S.; Gow, P.; Wigg, A.; Tallis, C.; Jeffrey, G.; George, J.; et al.
Summary: Background: Antiviral therapy for hepatitis C has the potential to improve liver function in patients with decompensated cirrhosis. Aims: To examine the virological response and effect of viral clearance in patients with decompensated hepatitis C cirrhosis all with MELD scores ≥15 following sofosbuvir/daclatasvir ± ribavirin. Methods: We prospectively collected data on patients who commenced sofosbuvir/daclatasvir for 24‐weeks under the Australian patient supply program (TOSCAR) and analysed outcomes including sustained viral response at 12 weeks (SVR12), death and transplant. Results: 108 patients (M/F, 79/29; median age 56years; Child‐Pugh 10; MELD 16; genotype 1/3, 55/47) received sofosbuvir/daclatasvir and two also received ribavirin. On intention‐to‐treat, the SVR12 rate was 70% (76/108). Seventy‐eight patients completed 24‐weeks therapy. SVR12 was achieved in 56 of these patients on per‐protocol‐analysis (76%). SVR12 was 80% in genotype 1 compared to 69% in genotype 3. Thirty patients failed to complete therapy. In patients achieving SVR12, median MELD and Child‐Pugh fell from 16(IQR15‐17) to 14(12‐17) and 10(9‐11) to 8(7‐9), respectively (P<.001). In those who died, MELD increased from 16 to 23 at death (P=.036). Patients who required transplantation had a significantly higher baseline MELD (20) compared to those patients completing treatment (16) (P=.0010). The odds ratio for transplant in patients with baseline MELD ≥20 was 13.8(95%CI 2.78‐69.04). Conclusions: SVR12 rates with sofosbuvir/daclatasvir in advanced liver disease are lower than in compensated disease. Although treatment improves MELD and Child‐Pugh in most patients, a significant proportion will die or require transplantation. In those with MELD ≥20, it may be better to delay treatment until post‐transplant.